PENGARUH KUALITAS PROGRAM, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN PESERTA PELATIHAN PADA LEMBAGA PELATIHAN SALIM EXCELLENCE CENTER (SEC) - Tino Agus Salim; Theresia Pradiani; Fathorrahman (Journal of Applied Management Studies, 2021)
Business competition is now a global phenomenon that occurs in the world and in Indonesia. Various regional, national, international companies were established to make economic changes in the country move so fast in this case start-ups. Based on data from the Ministry of Communication and Information of the Republic of Indonesia, in 2019 there were 2,193 start-ups in Indonesia, which grew significantly. Training providers are very important because many companies need to increase the capacity of their staff. Training providers are able to have a direct impact on company needs faster than formal education. Companies tend to choose training providers to train their staff with training programs that fit their needs. This study aims to determine 1) the effect of program quality on training participants' satisfaction; 2) The influence of service quality on the satisfaction of training participants; 3) The effect of price (training costs) on the satisfaction of training participants at the Salim Excellence Center (SEC) Training Provider. This type of research is a quantitative approach. The number of samples in this study were 70 respondents who were training participants at the Training Provider Salim Excellence Center (SEC) according to Slovin's calculations using the Non Probability Sampling technique with Purposive Sampling. This study uses multiple linear regression. The results of this study indicate: 1) The quality of the program has a significant effect on the satisfaction of the training participants; 2) Service quality has a significant effect on training participants' satisfaction; 3) Price (training costs) has no significant effect on the satisfaction of training participants at the Salim Excellence Center (SEC) Training Provider.